Scene-Setting Adverbials in BBC Documentary Films - Vyhnálková, Iveta (Univerzita Pardubice, 2018)
This bachelor thesis analyse 240 adjuncts which were used in the BBC documentary movies, classifies them based on their semantic category, form, position in a clause, and their sequences. Further, the theme and rheme function of adjuncts in the functional sentence perspective is assessed. At the end of the analysis, the findings are presented in the context of the commentary language.
Použití příslovečných určení v dokumentárních filmech BBC
Keywords: adjunkty; příslovečné určení; jazyk komentáře; funkční větná perspektiva; adjuncts; scene-setting adverbials; commentary language; functional sentence perspective